JingleOS: An Operating System to Embedded Devices with Language-Based Protection - Tenório, Luiz Eugênio Fernandes; Meira, Silvio Romero de Lemos (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2012)
Language based protection and high-level language virtual machines (JVM, CLR) have solved many problems of portability and dependability. Development of operating systems with these characteristics for embedded systems could enjoy these benefits with the solution of basic problems related to resource consumption and performance. This paper presents the JingleOS, an operating system designed on these concepts for devices with a few kibibytes of RAM and 8 bits microcontrollers. To support the system design, advanced compiler techniques and extensions of the Java programming language were used, in order to allow low-level hardware access and bare metal execution.